Adhesion and proliferation of cultured human aortic smooth muscle cells on polystyrene implanted with N+, F+ and Ar+ ions: correlation with polymer surface polarity and carbonization - Bacáková, L; Svorcík, V; Rybka, V; Micek, I; Hnatowicz, V; Lisá, V; Kocourek, F (Biomaterials, 1996)
Physicochemical surface properties and biocompatibility were studied in polystyrene (PS) implanted with 150 keV N+, F+ and Ar+ at doses ranging from 1 x 10(12) to 1 x 10(15) cm-2. Adhesion and proliferation of cultured human aortic smooth muscle cells (SMCs) on ion implanted PS were thoroughly examined for dependence on implanted dose and ion species and in close relation to polymer surface oxidation, surface polarity, concentration of conjugated double bonds and sheet resistivity. The surface polarity of PS was a smooth, increasing function of the implanted dose. However, the dependence of SMC population density on the implanted dose was found to be more complicated. After 18 h cultivation time (i.e. when only cell attachment and spreading took place), the number of adhered SMCs and their degree of spreading first increased with increasing ion dose, and after reaching a maximum at the dose of 5 x 10(12) cm-2, they decreased to original values. For doses above 5 x 10(14) cm-2, an increase in SMC population density and spreading was again observed. The first maximum in cell adhesion can be explained by slight increases in the surface polarity and wettability, optimal for cell adhesion, and the second maximum by progressive carbonization of the PS surface. After 96 h cultivation time (i.e. when the cells proliferated intensively), the dramatic dependence of the SMC population density on implanted dose is mostly smeared out. This observed dependence of SMC attachment, spreading and subsequent proliferation on the implanted dose was similar in all three ion species, but highest cell densities were achieved on PS implanted with F+ ions.
Keywords: Chemical Phenomena; kultivované buňky; Argon; Nitrogen; Cell Adhesion; Polystyrenes; Cations; uhlík; fluor; dusík; povrchové vlastnosti; Chemistry, Physical; buněčné dělení; fyzikální chemie; kationty; Cell Division; Spectrophotometry, Ultraviolet; chemické jevy; Oxidation-Reduction; svaly hladké cévní; Carbon; Muscle, Smooth, Vascular; Cells, Cultured; Surface Properties; kyslík; Humans; argon; Fluorine; buněčná adheze; oxidace-redukce; Oxygen; spektrofotometrie ultrafialová; polystyreny; lidé